Navigation and non-navigation CT scan of the sinuses: comparison of the effective doses of radiation in children and adults - Noémie Villemure-Poliquin; Mario Chrétien; Jacques E. Leclerc (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The advent of 3D navigation imaging has opened new borders to the endoscopic surgical approaches of naso-sinusal inflammatory and neoplastic disease. This technology has gained in popularity among otolaryngologists for endoscopic sinus and skull base surgeries in both adults and children. However, the increased tissue radiation required for data acquisition associated with 3D navigation protocols CT scans is a source of concern because of its potential health hazards. We aimed to compare the effective doses of radiation between 3D navigation protocols and standard protocols for sinus computed tomography (CT) scans for both the adult and pediatric population. Methods We performed a retrospective cohort study through electronic chart review of patients undergoing sinus CT scans (standard and 3D navigation protocols) from May 2019 to December 2019 using a Siemens Drive (VA62A) CT scanner. The effective dose of radiation was calculated in mSv for all exams. Average irradiation doses were compared using a Student’s T-Test or a Kruskall–Wallis test when appropriate. Results A total of 115 CT scans were selected for analysis, of which 47 were standard protocols and 68 were 3D navigation protocols CT scans. Among these, 31 exams were performed on children and 84 exams on adults. For the total population, mean effective dose in the non-navigation CT scans was 0.37 mSv (SD: 0.16, N = 47) and mean effective dose in the 3D navigation sinus CT group was 2.33 mSv (SD: 0.45, N = 68). The mean difference between the two groups was statistically significant 1.97 mSv (CI 95% − 2.1 to − 1.83; P < 0.0001). There was a sixfold increase in radiation with utilization of 3D navigation protocols. The ratio was identical when the pediatric as well as the adult subset of patients were analyzed. Conclusion In our center, utilization of 3D navigation sinus CT protocols significantly increases radiation exposure. Otolaryngologists should be aware of this significant increase and should attempt to decrease the radiation exposure of their patients by limiting unnecessary scan orders and by evaluating 3D acquisition protocols locally with radiation physicists. Level of evidence: Level IV. Graphical Abstract